2017
DOI: 10.1159/000489864
|View full text |Cite
|
Sign up to set email alerts
|

Association of Brain-Derived Neurotrophic Factor and Vitamin D with Depression and Obesity: A Population-Based Study

Abstract: Background: Depression and obesity are widespread and closely linked. Brain-derived neurotrophic factor (BDNF) and vitamin D are both assumed to be associated with depression and obesity. Little is known about the interplay between vitamin D and BDNF. We explored the putative associations and interactions between serum BDNF and vitamin D levels with depressive symptoms and abdominal obesity in a large population-based cohort. Methods: Data were obtained from the population-based Study of Health in Pomerania (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
1
27
1
Order By: Relevance
“…Based on the current literature one can only speculate whether BDNF has a protective role in response to the underlying cardiac pathophysiology or if this neurotrophin contributes to disease progression. We also previously reported a U-shaped relationship between BDNF and waist-to-hip ratio as a marker of visceral adiposity 24 . Hence, the directionality and causality between BDNF and cardiovascular disease is still undetermined and may be related to signal cross-talk.…”
Section: Discussionmentioning
confidence: 62%
“…Based on the current literature one can only speculate whether BDNF has a protective role in response to the underlying cardiac pathophysiology or if this neurotrophin contributes to disease progression. We also previously reported a U-shaped relationship between BDNF and waist-to-hip ratio as a marker of visceral adiposity 24 . Hence, the directionality and causality between BDNF and cardiovascular disease is still undetermined and may be related to signal cross-talk.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have shown that vitamin D is essential for normal brain development and function, and vitamin D deficiency has been linked with neurological disorders, including depression [36][37][38]. Vitamin D is also involved in the initial biosynthetic stages of serotonin, a neurotransmitter which has been implicated in both depression and the mechanism of action of antidepressant drugs [39].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is also involved in the initial biosynthetic stages of serotonin, a neurotransmitter which has been implicated in both depression and the mechanism of action of antidepressant drugs [39]. Vitamin D deficiencies have also been linked to obesity [38]. For example, studies have found inverse relationships of vitamin D with total body fat and metabolic syndrome [40].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations